Snx27 Deletion Promotes Recovery From Spinal Cord Injury by Neuroprotection and Reduces Macrophage/Microglia Proliferation - Zeng, Yuzhe; Wang, Nawen; Guo, Tiantian; Zheng, Qiuyang; Wang, Shuang; Wu, Songsong; Li, Xi; Wu, Jin; Chen, Zhida; Xu, Huaxi; Wang, Xin; Lin, Bin (Frontiers in Neurology, 2018)
Sorting nexin 27 (SNX27) is an endosome-associated cargo adaptor that is involved in various pathologies and development of neurological diseases. However, the role of SNX27 in spinal cord injury (SCI) remains unclear. In this study, we found that SNX27 was up-regulated in injured mice spinal cords by western blot and immunofluorescence. A comparative analysis of Basso mouse scale (BMS), footprint test and corticospinal tract (CST) tracing in Snx27+/+ and Snx27+/- mice revealed that haploinsufficiency of SNX27 ameliorated the clinical symptoms of SCI. Based on the results of western blot and immunofluorescence, mechanistically, we found that SNX27 deficiency suppresses apoptotic caspase-3 induced neuronal death. In addition, SNX27 haploinsufficiency lowers the infiltration and activation of macrophage/microglia by suppressing their proliferation at the SCI lesion site. Together, these results suggest that down-regulation of SNX27 is a potential therapy targeting both acute neuronal death and chronic neuroinflammation, and promoting nerve repair after SCI.